2017
DOI: 10.3390/buildings7030067
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of the Influence of Property Tax on Housing Prices in the Apulia Region (Italy)

Abstract: Abstract:In this research, the socio-economic determinants of housing market values have been examined, highlighting their respective contributions to the formation of the property prices and, in particular, verifying the property tax liability. The property tax is a factor that could determine, through modest fluctuations, the revival of the property demand, generating positive effects also on the construction sector, which has been currently affected by the negative real estate contingency. The functional co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 57 publications
1
21
0
Order By: Relevance
“…A specific application of a multi-objective genetic algorithm for the identification of the "best" regression models, named evolutionary polynomial regression, has been recently implemented to several property issues. Initially applied to hydraulic systems [94][95][96], the methodology has been borrowed and used to elicit the correlations between the property market and socio-economic variables [97,98], energetic factors [99], and for property tax purposes [100]. Other studies have allowed researchers to highlight the advantages of the methodology compared to orthodox [101] and innovative mass appraisal approaches [102].…”
Section: Background On the Main Mass Appraisal Techniquesmentioning
confidence: 99%
“…A specific application of a multi-objective genetic algorithm for the identification of the "best" regression models, named evolutionary polynomial regression, has been recently implemented to several property issues. Initially applied to hydraulic systems [94][95][96], the methodology has been borrowed and used to elicit the correlations between the property market and socio-economic variables [97,98], energetic factors [99], and for property tax purposes [100]. Other studies have allowed researchers to highlight the advantages of the methodology compared to orthodox [101] and innovative mass appraisal approaches [102].…”
Section: Background On the Main Mass Appraisal Techniquesmentioning
confidence: 99%
“…This method constitutes a generalization of the stepwise regression, that is linear with reference to the regression parameters and non-linear in the model structures. In particular, the method uses a genetic algorithm in order to iteratively investigate the model mathematical structures [66,68]. The key idea of the method is to search firstly for the best form of the function, i.e., a combination of vectors of independent variables (inputs), and then to perform least squares regression to find the adjustable parameters elevated by the appropriate exponents for each combination of inputs.…”
Section: Methodsmentioning
confidence: 99%
“…Tsatsaronis and Zhu [64] have demonstrated that taxes and hereditary expectations are short-term housing price determinants in many countries. López García and Tajani et al [65,66] have pointed out the influence of tax policies on the changes of housing prices respectively in Spain and in Italy.…”
Section: Introductionmentioning
confidence: 99%
“…. x n ) and to identify the explanatory factors most influential in the mechanisms for the formation of the housing prices in different territorial contexts [58,59] and to determine the marginal contribution of each of them on the prices. The application of EPR to the construction cost sector, therefore, reveals interesting and unexplored potentialities.…”
Section: Training Set Validation Set Training Set Validation Set Traimentioning
confidence: 99%